Strategic performance management system in uncertain business environment: An empirical study of the Indian oil industry. Issue 4 (2nd July 2018) - Akhtar, Mohammad; , Sushil
Abstract : Purpose: Business performance management describes the processes, methodologies, metrics and systems needed to measure and manage the performance of an enterprise. Traditional performance management systems were based on financial and productivity measures but the alternate measures proposed in last more 25 years have strategic focus and incorporate variety of performance measures such as efficiency, effectiveness, productivity, quality, customer satisfaction, innovation and employee satisfaction in addition to financial. Globalization and modernization have created a business environment uncertain with associated risks which has necessitated the incorporation of various types of flexibilities such as strategic, technical, operational, information system (IS), etc. Critical success factors and implementation issues also need to be incorporated to succeed. The purpose of this paper is to present the strategic performance management system (SPMS) designed, incorporating flexibility and implementation issues, and its effectiveness empirically validated from Indian oil industry. Design/methodology/approach: Based on literature review and gaps identified, a proposed model of enterprise performance management system incorporating flexibility, critical success factors and implementation issues was developed. Macro- and micro-level factors impacting the effectiveness of the model were identified, and hypotheses were developed and tested empirically from the survey study of Indian oil industry. Findings: The finding met, by and large, most of the research objectives. In total, 7 macro- and 11 micro-level factors came out from the study. The strategy planning, strategy implementation, strategic flexibility (SF), SPMS design, information system flexibility (IF) flexibility, implementation issues and critical success factors, and performance feedback and learning are the macro-level factors impacting the SPMS effectiveness in measuring and managing performance of an enterprise. The SPMS implementation issues have proved to be major driver of effectiveness. Research limitations/implications: The research like many such researches had limited resources, data availability and bias of respondents. However, the model was statistically validated for its reliability and hypothesis testing. The research has added to literature on SPMS as integrated model incorporated SF, information flexibility and critical success factors. However, the effect of other types of flexibilities such as organizational, operational, HR, marketing, etc., and other stakeholders should also be studied in future research to broaden the findings. Practical implications: The validated SPMS has practical implications for academics and researchers. Strategic and IF, and critical success factors have been incorporated in the integrated model to take care of business uncertainties so that it is strategically aligned and facilitate in effective SPMS use and implementation. Social implications: Though it has no direct social implication but, if adopted for social projects and not-for-profit organizations, it will have social benefits of efficient and effectiveness delivery of social projects and initiatives. Originality/value: This is an original work carried out by the authors. The validated model along with interpretation is presented.